“Un contexto para una masona, librepensadora, feminista y republicana: Belén de Sárraga (1872-1950)” - Hottinger Craig, Sylvia (2013)
Belén de Sárraga (1893-1950) a Freemason, Freethinker, Republican and Feminist left Spain in 1907 to settle and travel in Latin America. She publicized all the Freemason, Freethinkers, Republican and Feminist policies and ideas she had been fighting for in Spain. She also partook in the creation of a new idea, the Republican Confederation of Latin American countries through anticlericalism and revolution. Upon the proclamation of the II Republic (1931- 1939), de Sárraga returned to Spain to find the country’s politics enclosed into polarized political parties. This paper is an attempt to contextualize Belén de Sárraga within her times as these were obscured by the events that were to follow, namely, Spain’s Civil War and World War II.